Identification of Dendrobium Orchid Species in Nglurah, Karanganyar as a High School Biology Learning Resource - Agus Purwanto; Dian Andhi Saputra (Jurnal Biologi Tropis, 2026)
Biodiversity-based learning that utilizes local potential plays an important role in enhancing students’ understanding of biological concepts through direct interaction with real objects in their environment. This study aimed to identify Dendrobium orchid species found in Desa Nglurah, Tawangmangu District, Karanganyar Regency, and to analyze their potential as learning resources for senior high school biology, particularly on biodiversity topics. The research was conducted from May to August 2025 using a descriptive qualitative approach to describe field phenomena based on actual conditions. Data were collected through direct observations at several randomly selected sites and supported by descriptive notes, photographs, and records of morphological characteristics. Species identification was carried out using reference literature and Google Lens. Each encountered Dendrobium species was identified, and variations in flower morphology, color, and form were documented for classification purposes. The results revealed 26 Dendrobium orchid species classified into two main flower types: star-shaped flowers (22 species) and curly-shaped flowers (4 species). Flower color variations included white, pink, purple, golden brown, bluish purple, bright yellow, red, and bright green, most of which resulted from hybridization. These morphological variations reflect species-level biodiversity and align with senior high school biology learning outcomes. Therefore, Dendrobium orchids from Desa Nglurah have strong potential to be utilized as contextual and concrete learning resources. This study recommends further development of the identification results into biology learning media and teaching materials based on local potential.